Induced Innovation, Inventors, and the Energy Transition - Eugenie Dugoua; Todd D. Gerarden (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study how individual inventors respond to incentives to work on "clean" electricity technologies. Using natural gas price variation, we estimate output and entry elasticities of inventors and measure the medium-term impacts of a price increase mirroring the social cost of carbon. We find that the induced clean innovation response primarily comes from existing clean inventors. New inventors are less responsive on the margin than their average contribution to clean energy patenting would indicate. Our findings suggest a role for policy to increase the supply of clean inventors to help mitigate climate change.
Keywords: O31; Q55; Q40; 330; inventors; energy technology; induced innovation